As atribuições imputadas à sombra no trabalho de Catarina Mourão e de Lourdes Castro - Ferraz, Renata Christiane, 1979- (2018)
This article aims to reflect about the functions attributed to the aesthetic gesture of the shadow mobilization in the film titled ‘Through Shadows’ directed by Catarina Mourão and co-authored by Lourdes Castro. The meeting between the director and the visual artist brings us unusual paths offered to the shadows in the contemporary artistic representations